Absence of right superior vena cava and persistence of left superior vena cava in fetus: Presenting two cases. - Yamelic Bernal; Carlos García Guevara; Elsa F. Ruisanchez; Pablo Marantz; Carlos García Morejón; Andrés Savío Benavides (ECIMED, 2011)
Persistent Left Superior Vena Cava is the most common congenital vascular anomaly. In the vast majority of cases its persistence coincides with thepresence of the right superior vena cava. The absence of the latter with persistent left superior vena cava is a rare variant. We describe the ultrasonographicsigns that identify this rare malformation on fetus. The study was conducted in two pregnant women referred to the national reference center ofcongenital heart disease, showing a left superior vena cava draining into a dilated coronary sinus and the absence of right superior vena cava. Thepresence of a Persistent Left Superior Vena Cava with the absence of a Right Superior Vena Cava is a rare variant of systemic venous return that canbe diagnosed prenatally.